Plutarch's Unexpected Silences : Suppression and Selection in the Lives and Moralia - Beneker, Jeffrey; Cooper, Craig; Humble, Noreen; Titchener, Frances (Brill's Plutarch Studies, 2022)
The act of recording anything is at the same time an act of silencing. Choices are made at every step about what to keep and what to discard. Examining what Plutarch has left out enriches our understanding of what he has chosen to say, and both deepens our knowledge of the literary practices of this influential writer and opens new and fruitful lines of enquiry about Plutarch, his work, and his world.